Communication-Polysulfide-Induced Chemical Capacity Loss in Li-S Batteries - Kim, Kookhan; Kim, Chunjoong; Park, Jungjin; Sung, Yung-Eun (Electrochemical Society, Inc., 2022)
Time-dependent deterioration of the electrochemical performance in the lithium-sulfur (Li-S) cell is thoroughly revaluated. The degradation in the capacity and rate performance is highly affected by the irreversible chemical reaction of the sulfur cathode and Li anode with polysulfide intermediates. We newly propose the new data plot, the capacity vs test time, to better understand the relation between rate performance and cycle retention excluding the self-discharge effect.